A magyarországi és erdélyi városok etnikai homogenizációjának néhány aspektusa a 20. században - Balizs, Dániel; Bajmócy, Péter (Közép-Európai Közlemények, 2012)
The subject of our study is how the ethnical structure of Hungarian and Transylvanian cities changed in the 20th century. Our question is how experienced the rise of the nationstates and the homogenization of the urban population in national aspects. We can characterize the population of both areas with large ethnic diversity, because beside the stateforming nation significant numbers of minorities – Hungarians and Romanians, as well as Serbs, Slovaks, Germans, Croats, Roms - live in these territories. However the initial condition is similar, because each of these regions belonged to the Hungarian Kingdom at the early 20th century, but considering the process of the past century we find differences between the three countries and also within the country borders. During the research we took the ratio and the numerical changes of majority nations and the Hungarians into consideration. Over the compared census data from 1910 and 2001/2002, according to the specified criteria we differentiated types with the method of cluster analysis. The clusters are explicable, well representing the ethnic and demographic transformation of the two neighbouring countries’ towns, as well as the existing similarities and differences.